Influence of Source of Oil Added to Diet on Egg Quality Traits of Laying Quail - Al-Daraji , Hazim J.; Al-Mashadani, H.A.; Mirza, H.A.; Al-Hayani, W.K.; Al-Hassani, A.S. (International Journal of Poultry Science, 2011)
This experiment was performed to investigate the influence of different oils in the diets of laying quail on their egg quality characteristics. One hundred and twenty 7-wk old Japanese quails (Coturnix coturnix japonica) were allocated to four groups with three replicates containing 10 quail each (30 quail per each treatment group). They were fed for 13 weeks (including one week of adaptation period) on diets containing 3% oil from different sources, viz. either sunflower (T1), linseed (T2), maize (T3), or fish oil (T4). Inclusion the diet of laying quail with fish oil (T4) and maize oil (T2) resulted in significant increase with respect to egg weight, yolk weight, albumen weight, yolk diameter, yolk height, albumen diameter, albumen height, shell thickness and Haugh unit during all periods of experiment and in total means of these parameters. However, the addition of different oil sources used in this experiment to quail diets did not significantly affect total means of shell weight, relative weight of albumen and relative weight of shell, while total means of relative weight of yolk, yolk index and albumen index were higher in the birds receiving diets containing fish (T4) and maize (T2) oil than in other treatments (T1 and T3). The results of this experiment clearly demonstrated that supplementation the laying quail diet with fish and maize oil improved most criteria of egg quality. Therefore, incorporation of fish and maize oil into the diets of Japanese quail may have practical value in manipulating egg quality.